CONTAMINATION AND CHARACTERISTICS OF VISUAL SOLID WASTE IN COASTAL AMPALU DISTRICT NORTH PARIAMAN PARIAMAN CITY WEST SUMATRA - Devid Joehari; Sofyan Husein Siregar; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in Agust 2015 at coastal Ampalu district NorthPariaman Pariaman City West Sumatra Province. T he purpose of this study was todetermine the level of contamination and the characteristics of solid waste. Thesurvey methode was applied in this research whicht are 2 station observation alongthe coast Ampalu then be calculated and weighed according to characteristic solidwaste.The results of research shaun that the solid waste in coastal Ampalu wascategorised in to lees contaminated (category B) and fairly contaminated (categoryC). Where the at station 1 lees contaminated, and then Station 2 is relative fairlycontaminated of visually, that generally solid waste consisted of plastics, paper,rubber, foam, jute sacks, leaves, and small pieces of wood. All Solid wasteindetyfield originated from land base waste.Key words : Contamination, characteristics, solid waste, coastal Ampalu